Realizing high efficiency 532 nm laser by optimizing the mode- and impedance-matching. (21st December 2020) - Yao, Wenxiu; Wang, Qingwei; Tian, Long; Li, Ruixin; Shi, Shaoping; Wang, Jinrong; Wang, Yajun; Zheng, Yaohui
Abstract: Increasing the conversion efficiency of second harmonic generation (SHG) is an area of interest in research. We report a high-efficiency 532 nm laser generation, with a conversion efficiency of 94.04 ± 0.115% from the pump depletion of 98.1% ± 0.1%, by accurately quantifying the round-trip loss and the transmissivity of the input mirror using our proposed scheme. The optimal conversion efficiency of the cavity-enhanced frequency doubling process is independent of the waist and is determined by the pump depletion, round-trip loss, and transmissivity of the input mirror. These results show that the cavity-enhanced frequency doubling process is not necessary to set the focusing parameter at the optimal single-pass conversion. These results provide a guide for future research on high-efficiency SHG.